On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera: Scarabaeidae: Melolonthinae) - Bezděk, Aleš; Kalashian, Mark; Ghrejyan, Tigran (Zootaxa, 2019)
The melolonthine species Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera: Scarabaeidae: Melolonthinae: Melolonthini) was described from three specimens collected by Dmitriy M. Maljuzhenko, a physician by profession, while he was working in the former Erivan Governorate from 1906 to at least 1914 (Anonymous 1914). Type series was cited by Zaitzev (1928) differently in the Russian and in German versions of the primary description. In the Russian version, Zaitzev stated on p. 393 in Cyrillic script: “Arm. Alishar u Araksa (3 ekz. Maljuzhenko, koll. Muz. Eriv. univ. i Muz. Gruzii)”, while in the German version, he mentioned on p. 397: “Nachkraj: Alishar, distr. Sharur (3 ♀♀, dr. Maljuzhenko, Koll. d. Museen Georgien und Armenien)”. At the time of collecting the type specimens (no later than 1914 when Maljuzhenko finished his collecting activity in the region (S.M. Iablokoff-Khnzorian, personal communication to M.K. in 1993)), the locality was a part of the Erivan Governorate of the Russian Empire. Currently, it is situated in the Nakhichevan Autonomous Republic of Azerbaijan.